InPBi single crystals grown by molecular beam epitaxy - Wang, Kai; Gu, Yi; Zhou, H. F.; Zhang, Liyao; Kang, C. Z.; Wu, Mingjian; Pan, Wenwu; Lu, P. F.; Gong, Qian; Wang, Shumin (Scientific Reports, 2014)
InPBi was predicted to be the most robust infrared optoelectronic material but also the most difficult to synthesize within In-VBi (V = P, As and Sb) 25 years ago. We report the first successful growth of InPBi single crystals with Bi concentration far beyond the doping level by gas source molecular beam epitaxy. The InPBi thin films reveal excellent surface, structural and optical qualities making it a promising new III-V compound family member for heterostructures. The Bi concentration is found to be 2.4 ± 0.4% with 94 ± 5% Bi atoms at substitutional sites. Optical absorption indicates a band gap of 1.23 eV at room temperature while photoluminescence shows unexpectedly strong and broad light emission at 1.4-2.7 μm which can't be explained by the existing theory. <embed height="0" id="xunlei_com_thunder_helper_plugin_d462f475-c18e-46be-bd10-327458d045bd" type="application/thunder_download_plugin" width="0"></embed>